Prispevek nobelovcev k razvoju medicine v prvi polovici 20. stoletja - Zupanič Slavec, Zvonka (Medicinski razgledi, 2003)
The article discusses the significance of various natural science discoveries in the development of medicine during the first half of the 20th century. Discoveries in various areas of natural science, for which the authors were awarded the Nobel Prize, have been selected. Almost twenty Nobel prizewinners are presented through their core life's work. Among these are Behring, discoverer of the diphtheria vaccine; Roentgen, discoverer of X-rays; Finsen, discoverer of the significance of UV rays; Curie-Sklodowska, discoverer of theelements radium and polonium; Koch, discoverer of tuberculosis and cholera pathogens; Cajal, who pioneered research into the physiological phenomena of the central nervous system; Ehrlich, originator of the immunity theory; Kocher, pioneer of thyroid surgery; Richet, discoverer of the cause of anaphylaxis; Pregl, originator of microchemical analysis; Jauregg, discoverer of treatment of late forms of syphilis by malaria agents; Nicolle, discoverer of the typhus pathogen carrier (lice); Landsteiner, discoverer of blood groups; Domagk, discoverer of prontosil; Whipple, discoverer of pernicious anemia treatment by a liver diet; and Fleming, discoverer of penicillin.
Keywords: Nobel Prize; Nobelova nagrada; History Of Medicine, 20th Cent.; Zgodovina medicine 20.stoletja; medicina; medicine; zgodovina medicine; nobelovi nagrajenci